2004
DOI: 10.1080/10473289.2004.10471003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effectiveness of Precursor Reductions in Lowering 8-Hr Ozone Concentrations—Part II. The Eastern United States

Abstract: Analyses of ozone (O 3 ) measurements in conjunction with photochemical modeling were used to assess the feasibility of attaining the federal 8-hr O 3 standard in the eastern United States. Various combinations of volatile organic compound (VOC) and oxides of nitrogen (NO x ) emission reductions were effective in lowering modeled peak 1-hr O 3 concentrations. VOC emissions reductions alone had only a modest impact on modeled peak 8-hr O 3 concentrations. Anthropogenic NO x emissions reductions of 46 -86% of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Mechanistic understanding derived from field and modeling studies, complemented by studies of ambient VOC and NO x trends in specific regions, supports the conclusion that the relationship in Figure 3 depicts causal relationships (Sillman et al, 1990;Trainer et al, 1993Trainer et al, , 2000Kleinman, 2000). Modeling studies showed that lowering peak 8-hr O 3 concentrations in multiple subregions of central California and the eastern United States to values in the range of 60-70 ppbv would require NO x emission reductions in the range of 80% to over 90% from 1996-1999 emissions (Reynolds et al, 2003(Reynolds et al, , 2004. In these studies, large (>80% from late 1990s levels) reductions of NO x emissions are required for lowering peak 8-hr O 3 concentrations, in part because the effectiveness of the mass reduction of NO x is partially offset by increasing O 3 production efficiency at lower ambient concentrations of NO x (Reynolds et al, 2004).…”
Section: The Role Of No Xmentioning
confidence: 64%
“…Mechanistic understanding derived from field and modeling studies, complemented by studies of ambient VOC and NO x trends in specific regions, supports the conclusion that the relationship in Figure 3 depicts causal relationships (Sillman et al, 1990;Trainer et al, 1993Trainer et al, , 2000Kleinman, 2000). Modeling studies showed that lowering peak 8-hr O 3 concentrations in multiple subregions of central California and the eastern United States to values in the range of 60-70 ppbv would require NO x emission reductions in the range of 80% to over 90% from 1996-1999 emissions (Reynolds et al, 2003(Reynolds et al, , 2004. In these studies, large (>80% from late 1990s levels) reductions of NO x emissions are required for lowering peak 8-hr O 3 concentrations, in part because the effectiveness of the mass reduction of NO x is partially offset by increasing O 3 production efficiency at lower ambient concentrations of NO x (Reynolds et al, 2004).…”
Section: The Role Of No Xmentioning
confidence: 64%
“…For example, a report by the Instituto Nacional de Ecología (INE) in Mexico (McKinley et al, 2003) found that the implementation of several control measures could achieve a 3% reduction in daily maximum ozone concentration at the cost of approximately two billion dollars. Regulatory action is initiated by the U.S. EPA when measured O 3 concentrations in an urban area exceed a certain threshold (see Reynolds et al, 2004, for recent discussion of one-hour and eight-hour averaged daily maxima standards); this is referred to as "non-attainment". Hundreds of U.S. counties are either close to the threshold or already in non-attainment, and it has been suggested that up to half of the non-attainment Published by Copernicus GmbH on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling studies confirm the importance of the increase in O 3 production efficiency as NO x emissions decline. 31 The ratios of O 3 /NO y or O 3 /NO x were also higher on weekends than on Wednesdays at other monitoring sites. Ratios of O 3 /CO were greater on Sundays compared with Wednesdays at the three locations having CO data (Jefferson Street, Yorkville, and DeKalb), and on Saturdays relative to Wednesdays at Jefferson Street and DeKalb.…”
Section: Voc/no Xmentioning
confidence: 92%